Influence of sonic vibration and cement type on the bond strength of fiberglass posts after aging. - Rayane Alexandra Prochnow; Rafaella Ronchi Zinelli; Luiz Carlos Machado Miguel; Leonardo Fernandes da Cunha; Gisele Maria Correr; Carla Castiglia Gonzaga; School of Health Sciences, Graduate Program of Dentistry, Universidade Positivo, Curitiba, PR, Brazil (Universidad de Concepción., 2020)
Introduction: This study evaluated the influence of sonic vibration and thermocycling on the bond strength of fiberglass posts using conventional dual-cured and self-adhesive resin cements. Material and Methods: Ninety-six single-rooted endodontically treated teeth were divided randomly into eight groups according to the cement used (dual-cured or self-adhesive resin cement), use of sonic vibration during post accommodation, and aging conditions (24h in distilled water or 5,000 thermal cycles). The fiberglass posts (White Post DC1, FGM) were cleaned with alcohol, treated with silane and cemented with dual-cured (Allcem Core, FGM) or with self-adhesive resin cement (seT, SDI). For groups in which sonic vibration was used, the posts were accommodated, and sonic vibration was applied for 10 s using a special tip placed on top of the post (Sonic Smart Device, FGM). Pull-out tests were performed after storage in distilled water for 24h at 37°C or after thermocycling (5000 cycles, at 5°C and 55°C). The results were evaluated using three-way ANOVA and Tukey's test (α=0.05). Results: Significant differences were not observed between the bond strengths of dual-cured (87.93±41.81 N) and self-adhesive cement (82.53±41.43 N). Bond strength for the sonic vibration groups (100.36±42.35 N) was significantly higher than for groups without sonic vibration (70.13±34.90 N). There were significant differences between specimens subjected to thermocycling (98.33±39.42 N) and those stored for 24h in distilled water (72.16±39.67 N). Conclusion: It can be concluded that both sonic vibration and thermocycling significantly improved bond strength of fiberglass posts with the two evaluated resin cements.